PKM Peningkatan Kompetensi Guru dalam Proses Identifikasi Siswa Berkebutuhan Khusus di SLB Aisyiyah Porong - Nurfi Laili; Zaki Nurfahmawati; Kemil Wachidah (Universitas Mathla'ul Anwar Banten, 2022)
COMMUNİTY SERVİCES: IMPROVİNG TEACHER COMPETENCE İN THE IDENTİFİCATİON PROCESS OF STUDENTS WİTH SPECİAL NEEDS AT SLB AİSYİYAH PORONG. Special school (SLB) is a form of formal education that is devoted to managing students who have special needs both in terms of development and academics. The various types of disabilities or special needs of these students require a thorough and comprehensive theoretical understanding of the behavioral characteristics of each type. This makes every teacher who teaches in special schools is required to have the ability and sensitivity in identifying students based on their distinctive behavioral characteristics. Whereas in SLB 'Aisyiyah Porong, in practice there is still no system for identifying students with special needs who register as new students based on the distinctive characteristics of each student. So that the need for competency development is related to theoretical understanding and then the practice of identifying prospective students becomes greater. This can be used as an initial milestone in the development of appropriate learning tools and according to the characteristics and abilities of each student